The Missing Link Between Corporate Social Responsibility and Consumer Trust: The Case of Fair Trade Products - Castaldo, Sandro (Journal of business ethics, 2009)
This paper investigates the link between the consumer perception that a company is socially oriented and the consumer intention to buy products marketed by that company. We suggest that this link exists when at least two conditions prevail: (1) the products sold by that company comply with ethical and social requirements; (2) the company has an acknowledged commitment to protect consumer rights and interests. To test these hypotheses, we conducted a survey among the clients of retail chains offering Fair Trade products. The results show that socially oriented companies can successfully leverage their reputation to market products with high symbolic values.